2020
DOI: 10.1088/2051-672x/ab96db
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Self-Assembled Monolayer and Characterization of AA7075-T6/B4C Nano-ceramic surface composite using Friction Stir Processing

Abstract: In the present study, fabrication of surface composite using AA7075-T6 as a matrix material and boron carbide nanoparticles as reinforcement through Friction stir processing (FSP) has been done. FSP technique has been widely utilized for surface modification and the formation of composite material. The B 4 C nanoparticles size (<30 nm) as reinforcement were padded in dimension of 2 mm width and 1.5 mm depth groove of AA7075-T6 plate as a matrix material. The single-pass process executed using a square tool pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…SEM micrographs also shows that in processed matrices the grains are well refined and very few cavities are present. Similar results were reported by Butola et al 27 in their study. It can also be observed that grain size decreases with the increasing tool rotational speed up to 1200 r/min, and on further increasing the tool rotational speed nanoparticle reinforcement starts agglomerating.…”
Section: Methodssupporting
confidence: 93%
“…SEM micrographs also shows that in processed matrices the grains are well refined and very few cavities are present. Similar results were reported by Butola et al 27 in their study. It can also be observed that grain size decreases with the increasing tool rotational speed up to 1200 r/min, and on further increasing the tool rotational speed nanoparticle reinforcement starts agglomerating.…”
Section: Methodssupporting
confidence: 93%
“…Composites are defined as a multiphase system that consists of two different groups of materials, one is the matrix and another is reinforcement, which is chemically and physically distinct and separated by interfaces (Kumar et al , 2018; Butola et al , 2020d). Nowadays, aluminium metal matrix composites (AMMCs) are finding wide application in automobile, marine, aerospace, defense and even in the nuclear industry (Butola et al , 2020a; Tyagi et al , 2021). AMMCs are preferred over aluminium alloys because of their excellent strength-to-weight ratio (Butola et al , 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Al, Mg, Steel, and Ti-based alloys are used for surface composites. Butola et al [44] successfully fabricated the SAM (Self-Assembled Monolayer) technique of Al-B4C nano-ceramic surface composite by implementing FSP. The mechanical properties of fabricated nano-ceramic surface composites on evaluation after one pass exhibited higher hardness, ultimate tensile strength, and finer grain structure in comparison to the base metal (BM).…”
Section: Surface Compositesmentioning
confidence: 99%